A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

Effects of different growth patterns of Tamarix chinensis on saline-alkali soil: implications for coastal restoration and management - Chen Gu; Weibin Huang; Qing Shao; Jiyan Shi; Jianliang Rui; Yanming Yu; Zhinai Lu; Yao Chen; Xiaojun Chen; Shudi Dong; Chenghua Ye; Ya Tuo (Biotechnology Letters, 2022)

Halophyte Vegetation Influences Soil Microbial Community of Coastal Salt Marsh - Chen Gu; Jiyan Shi; Jianliang Rui; Yanming Yu; Weibin Huang; Zhinai Lu; Yao Chen; Xiaojun Chen; Shudi Dong; Zhijun Hu; Chenghua Ye (Journal of Ocean University of China, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Bioaccessibility of microplastic-associated heavy metals using an in vitro digestion model and its implications for human health risk assessment - Xue-juan Chen; Jin-jin Ma; Rui-lian Yu; Gong-ren Hu; Yu Yan (Environmental Science and Pollution Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Genome-wide analysis of Keratinibaculum paraultunense strain KD-1 T and its key genes and metabolic pathways involved in the anaerobic degradation of feather keratin - Weidong Wu; Shichun Ma; Rui Chen; Yan Huang; Yu Deng (Archives of Microbiology, 2022)

The protective effects of procyanidin supplementation on PM2.5-induced acute cardiac injury in rats - Bowen Yin; Xiao Zhang; Jingyi Ren; Fengge Chen; Jufeng Liang; Hanning Zhang; Huanting Pei; Zhaohui Hu; Yan Wang; Wei Xue; Xinyue Yu; Rui Zhang; et al. (Environmental Science and Pollution Research, 2022)

Maternal obesity induces liver lipid accumulation of offspring through the lncRNA Lockd/mTOR autophagy pathway - Rui Chen; Hongguang Yang; Yong Song; Hongjie Yu; Minzhe Zhang; Weiming Rao; Yaxu Wang; Xiaoyue Xiao; Qiutong Chen; Qiqiang He (Molecular Genetics and Genomics, 2022)

Long non-coding RNA RPL34-AS1 ameliorates oxygen–glucose deprivation-induced neuronal injury via modulating miR-223–3p/IGF1R axis - Xin-ya Wei; Tian-qi Zhang; Rui Suo; You-yang Qu; Yan Chen; Yu-lan Zhu (Human Cell, 2022)

Strength and microstructural characteristics of cement-solidified salt-rich dredged silt modified by nanoparticles - Shiquan Wang; Lei Lang; MingLi Wei; Xingxing He; Rui Wang; Chen Yu; Songbao Feng; Zhiyong Niu; Hongrui Ma (Marine Georesources & Geotechnology, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Hierarchical collagen fibers complexed with tannic acid and Fe3+ as a heterogeneous catalyst for enhancing sulfate radical-based advanced oxidation process - Rui Wang; Ruiquan Yu; Junchao Wang; Jun Xiang; Chaojian Chen; Gongyan Liu; Xuepin Liao (Environmental Science and Pollution Research, 2022)

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

A Multi-Source Convolutional Neural Network for Lidar Bathymetry Data Classification - Yiqiang Zhao; Xuemin Yu; Bin Hu; Rui Chen (Marine Geodesy, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

A Strategy for the Effective Optimization of Pharmaceutical Formulations Based on Parameter-Optimized Support Vector Machine Model - Siqi Wang; Jianping Yang; Hengwei Chen; Kexin Chu; Xuefei Yu; Yaqiong Wei; Haixia Zhang; Mengjie Rui; Chunlai Feng (AAPS PharmSciTech, 2022)